A REVIEW ARTICLE ON SANDHIVATA W.S.R. TO OSTEOARTHRITIS - Dr. Suman Shekhawat (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2017)
VataVyadhi is a specific group of Vataja disorders, which can be produced only by the vitiation of Vata. Acharya Charaka has mentioned NanatmajaVyadhi of Vata, Pitta and Kapha, but a separate chapter has been contributed to only VataVyadhi. Acharya Vagbhatta has considered VataVyadhi as a “Maharoga”. This denotes that the Acharya has given importance to Vata as it dominates in the function and is supposed to be the leader of the remaining two Dosha. Acharya Sharangadhara states that Pitta and Kapha are action less (Pangu) unless and until they are activated by Vata. Due to this reason Vatika disorders are difficult to cure and some of them are serious in nature, while other take a chronic course and make the patient cripple thus burden to family and society.